Maintenance of Environmental Sustainability Through Microbiological Study of Pharmaceutical Solid Wastes. Issue 3 (14th December 2015) - Chowdhury, Fouzia Ferdous Khan; Acharjee, Mrityunjoy; Noor, Rashed
Abstract : Untreated waste materials discharged from the pharmaceutical industries due to lack of legislative regulations may cast the unfavorable consequences within the environment. The present study endeavored to stress the proliferation of harmful microorganisms in both treated and untreated pharmaceutical wastes along with the assessment of the drug resistance patterns of the isolates. The existence of the total viable bacteria and fungi was estimated up to 10 9 and 10 6 colony forming unit (cfu)/mL, respectively, in treated pharmaceutical wastes. For the untreated wastes, the bacterial and the fungal load were 10 6 and 10 3 cfu/mL, respectively. Both categories of samples were found to be contaminated with an array of pathogenic bacteria including Klebsiella spp., Vibrio spp., Bacillus spp., and Staphylococcus spp. Interestingly, an elevated range of pathogenic contamination was noticed in the treated samples up to 10 5 cfu/mL while a comparatively reduced microbial load was observed in the untreated samples within a range of 10 2 –10 4 cfu/mL. Most of the isolates exhibited resistance against commonly used antibiotics while several isolates showed multi‐drug resistance. Conversely, almost all untreated samples were found to exhibit in vitro anti‐bacterial activity against eight categories of laboratory isolates tested. Abstract : Proliferation of multi‐drug resistant microorganisms was observed to be higher within treated pharmaceutical wastes compared to untreated wastes. The untreated wastes were found to exhibit significant antimicrobial activity. The transfer of the drug‐resistance property from Klebsiella spp. into Escherichia coli was noticed, indicating the possibility of dissemination of drug‐resistant microorganisms within the environment.